Combination Trimodality Therapy Using Vismodegib for Basal Cell Carcinoma of the Face - Alec M. Block; Fiori Alite; Aidnag Z. Diaz; Richard W. Borrowdale; Joseph I. Clark; Mehee Choi (Case Reports in Oncological Medicine)
Background. For large basal cell carcinomas (BCCs) of the head and neck, definitive surgery often requires extensive resection and reconstruction that may result in prolonged recovery and limited cosmesis. Vismodegib, a small-molecule inhibitor of the hedgehog pathway, is approved for advanced and metastatic BCCs. We present a case of advanced BCC treated with combination of vismodegib, radiotherapy, and local excision resulting in excellent response and cosmesis. Case Presentation. A 64-year-old gentleman presented with a 5-year history of a 7 cm enlarging right cheek mass, with extensive vascularization, central ulceration, and skin, soft tissue, and buccal mucosa involvement. Biopsy revealed BCC, nodular type. Up-front surgical option involved a large resection and reconstruction. After multidisciplinary discussion, we recommended and he opted for combined modality of vismodegib, radiotherapy, and local excision. The patient tolerated vismodegib well and his right cheek lesion decreased significantly in size. He was then treated with radiotherapy followed by local excision that revealed only focal residual BCC. Currently, he is without evidence of disease and has excellent cosmesis. Conclusions. We report a case of locally advanced BCC treated with trimodality therapy with vismodegib, radiotherapy, and local excision, resulting in excellent outcome and facial cosmesis, without requiring extensive resection or reconstructive surgery.